“the Phenomenon Of Violence And Aggression From Stands To The Field In The Football Stadiums And Surroundings Of Algerian Football - Mokrane , Smail (sports creativity, 2025)
In general and of football in particular is seen as a means of promoting the societies from which they obtain health, material benefits and psychological comfort. It has therefore become a social phenomenon which is developing day by day in practice. However, the phenomenon of sports violence is an obstacle to its development, and its reasons may be due to the players themselves, or to the sports public, and this may be due to other reasons. It can be caused by the desire to win, or by the decisions of some referees or the social status of certain young people. - All these data highlight the problem of the "phenomenon of violence and aggression in Algerian football stadiums". The multiplicity of factors represented in the role of the players, the public and the conduct of the referees is a hypothesis of stadium violence. The importance of research stems from the fact that the phenomenon concerns progress and keeps pace with developed countries. As for the objectives, it focused on raising awareness and highlighting the gravity of the phenomenon and its negative effects. On Algerian football.